Differential expression of seven conserved microRNAs in response to abiotic stress and their regulatory network in Helianthus annuus - Ebrahimi Khaksefidi, Reyhaneh; Mirlohi, Shirin; Khalaji, Fahimeh; Fakhari, Zahra; Shiran, Behrouz; Fallahi, Hossein; Rafiei, Fariba; Budak, Hikmet; Ebrahimie, Esmaeil (Frontiers in Plant Science, 2015)
Biotic and abiotic stresses affect plant development and production through alternation of the gene expression pattern. Gene expression itself is under the control of different regulators such as miRNAs and transcription factors (TFs). MiRNAs are known to play important roles in regulation of stress responses via interacting with their target mRNAs. Here, for the first time, seven conserved miRNAs, associated with drought, heat, salt and cadmium stresses were characterized in sunflower. The expression profiles of miRNAs and their targets were comparatively analyzed between leaves and roots of plants grown under the mentioned stress conditions. Gene ontology analysis of target genes revealed that they are involved in several important pathways such as auxin and ethylene signaling, RNA mediated silencing and DNA methylation processes. Gene regulatory network highlighted the existence of cross-talks between these stress-responsive miRNAs and the other stress responsive genes in sunflower. Based on network analysis, we suggest that some of these miRNAs in sunflower such as miR172 and miR403 may play critical roles in epigenetic responses to stress. It seems that depending on the stress type, theses miRNAs target several pathways and cellular processes to help sunflower to cope with drought, heat, salt and cadmium stress conditions in a tissue-associated manner.